Effects of Repeated Cryopreservation of Cleavage-Stage Embryos on Pregnancy and Perinatal Outcomes of Single Embryo Transfer - Yali Wang; Dongjia Chen; Bing Cai; Dan Huang; Yanwen Xu; Chenhui Ding (Clinical and Experimental Obstetrics & Gynecology)
Background: Embryo cryopreservation is an important part of assisted reproductive technologies to increase cumulative pregnancy rate in clients. However, in clinical settings, embryos can be subjected to repeated cryopreservation-warming cycles due to certain clinical circumstances. There are limited data on the effect such cycles may have on the success of embryo transfer procedures. In this study, we investigated the effect of repeated cryopreservation of cleavage-stage embryos on the pregnancy and perinatal outcomes of frozen embryo transfer (FET). Methods: We retrospectively collected data on single cleavage-stage embryo transfer (ET) cycles performed in our center from January 2017 to August 2021 and identified 98 cycles of repeated cryopreservation-warming in cleavage-stage ET cycles. Propensity score matching was conducted according to the age of the patients, body mass index, endometrial thickness, type of oocyte retrial cycle, and quality of the transplanted embryos to match once-cryopreserved cleavage-stage ET cycles in our center at a ratio of 1:3 (caliper value 0.01). Finally, 294 once-cryopreserved cleavage-stage ET cycles were set as controls. Clinical pregnancy, early miscarriage, live birth rates, and other pregnancy and perinatal outcomes were compared between the two groups. Results: Similar success rates were obtained with twice-cryopreserved embryo transfers (n = 98) and with once-cryopreserved embryo transfers (n = 294). Importantly, there was no significant difference in the clinical pregnancy, early miscarriage, and live birth rates as well as perinatal outcomes such as preterm birth and pregnancy complication rates between the two groups. There were no birth defects in the two groups. Conclusions: Repeated cryopreservation may not negatively affect pregnancy and perinatal outcomes of single cleavage-stage ET and may present a safe option for resuscitated cleavage-stage embryos that have been canceled for transfer.